Natura sive Deus. La Nature – Oikos, Mère, Dieu –, entre Imamichi, Dufrenne, Spinoza - Chiore, Valeria (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2020)
According to Spinoza concept of Deus sive Natura, this contribution aims to analyze the centrality of Nature (as Oikos, Mother, God) both in its ontological radicality and in its transcendental, aesthetic and ethical development. The analysis will move along the parallel tracks followed by two great philosophers of the twentieth century, Dufrenne and Imamichi who promoted a perfect balance between western philosophy and eastern meditation. In this way, whereas the Japanese philosopher Tomonobu Imamichi (1922/2012) focused his study on the radicality of Nature in relation to technique, aesthetics and ethics, Mikel Dufrenne (1910/1995), among the maximum representatives of French phenomenology, explored the ontological and transcendental implications evoking the suggestion of a Mother Nature that generates nature, thought, poetry. Keywords: Nature, ontology, technique, aesthetic, ethics